Determinant analysis of bullying among school-age children in Yogyakarta, Indonesia - Nina Dwi Lestari; Ensi Qoriati Ningrum; Karisma Puspita Tri Anggraini (Universitas Aisyiyah Yogyakarta, 2020)
Bullying is a very common, complex, and potentially damaging among school-age children. This incidence has increased from year to year, especially in Yogyakarta. This study aims to determine the factors that influence the occurrence of bullying among school-age children in Yogyakarta. The research method used was quantitative with a cross-sectional design in 114 school-age children in the elementary schools in Yogyakarta. The samples were taken by simple random sampling technique. The research instrument uses a questionnaire. Data were analyzed using the Chi-Square Test. The results showed that the bullying incidence was 51.8% dominated by the type of physical bullying which amounted to 62.7%. There were no significant relationship between sex (p-value = 0, 490), parenting style (p-value = 0778) with the incidence of bullying in school-age children. There were significant relationships between school factors (p-value = 0.001), peers (p-value = 0.024), intensity of watching television shows (p-value = 0.026) with the incidence of bullying in school-age children. It is expected that schools and community health nurses have a role in controlling bullying that occurs in schools